2022
DOI: 10.3389/fpsyg.2022.903508
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Boundaries of Disease—Significant Post-traumatic Growth in Multiple Sclerosis Patients and Caregivers

Abstract: Despite the negative repercussions of a chronic disease, multiple sclerosis (MS) might also lead to positive consequences. This longitudinal study explored post-traumatic growth in MS patients and attempted to identify possible determinants. Post-traumatic growth of 260 patients and their caregivers was compared. A subset of 209 patients and caregivers were evaluated at baseline. Patients filled in the Posttraumatic Growth Inventory and General Health Questionnaire at three different times over a 36-month foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…However, there is a lack of studies exploring these associations over a longer period. Longitudinal data indicate an increasing progression of PTG in MS and corroborate the influence of clinical, demographic, and mental health variables with small to medium effect sizes [19]. When studying personal benefit finding, an improvement tendency over time was also observed suggesting that substantial improvement of personal growth appears later in MS adaptation [17].…”
Section: Introductionmentioning
confidence: 52%
“…However, there is a lack of studies exploring these associations over a longer period. Longitudinal data indicate an increasing progression of PTG in MS and corroborate the influence of clinical, demographic, and mental health variables with small to medium effect sizes [19]. When studying personal benefit finding, an improvement tendency over time was also observed suggesting that substantial improvement of personal growth appears later in MS adaptation [17].…”
Section: Introductionmentioning
confidence: 52%
“…As described above, previous studies indicated that PTG in the context of neurological disorders may increase over time [ 16 , 17 ]. Since one-third of the patients in our study had suffered a previous TIA and 11.8% had suffered a previous ischemic stroke before the current TIA, it can be assumed that in these patients PTG might have developed already before the current TIA.…”
Section: Discussionmentioning
confidence: 97%
“…A higher level of PTG was found in the latter group, which indicates that PTG after traumatic brain injury is not only a common phenomenon but also seems to increase over time [ 16 ]. A recent study by Gil-Gonzales et al analyzed the longitudinal course of PTG in a group of patients with multiple sclerosis [ 17 ]. It was shown that the level of PTG increased over a follow-up period of 36 months; furthermore, the positive psychological changes were still present 12 years after the initial diagnosis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations